Impact Analysis of Solutions for Chronic Disease Prevention and Management 10th International Conference on Smart Homes and Health Telematics, ICOST 2012, Artiminio, Italy, June 12-15, 2012. Proceedings - Donnelly, Mark.; Paggetti, Cristiano; Nugent, Chris; Mokhtari, Mounir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Smart Homes and Health Telematics, ICOST 2012, held in Artiminio, Tuscany, Italy, June 12- 15, 2012. The 25 revised full papers presented together with 22 short papers were carefully reviewed and selected from 74 submissions. The papers are categorized into a number of sessions that include: User Engagement for Improved Adoption of Assistive Technologies, Self-Management and Tele-Rehabilitation, Advances in Remote Monitoring and Activity Recognition, Sensor Networks for Unobstrusive Monitoring Solutions, and Real World (3z(BAware(3y (BSystems.s
Keywords: Computer science; Special purpose computers; User interfaces (Computer systems).; Artificial intelligence; Image processing; Pattern recognition; Computer Science; Special Purpose and Application-Based Systems; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Pattern Recognition; Electronic books